B and T Cell Phenotypic Profiles of African HIV-Infected and HIV-Exposed Uninfected Infants: Associations with Antibody Responses to the Pentavalent Rotavirus Vaccine - Weinberg, Adriana; Lindsey, Jane; Bosch, Ronald; Persaud, Deborah; Sato, Paul; Ogwu, Anthony; Asmelash, Aida; Bwakura-Dangarambezi, Mutsa; Chi, Benjamin H.; Canniff, Jennifer; Lockman, Shahin; Gaseitsiwe, Simani; et al. (Frontiers in Immunology, 2018)
We examined associations between B and T cell phenotypic profiles and antibody responses to the pentavalent rotavirus vaccine (RV5) in perinatally HIV-infected infants (PHIV) on antiretroviral therapy and in HIV-exposed uninfected infants (PHEU) enrolled in IMPAACT P1072 study (NCT00880698). Of 17 B and T cell subsets analyzed, PHIV and PHEU differed only in the number of CD4+ T cells and frequency of naive B cells, which were higher in PHEU than in PHIV. In contrast, the B and T cell phenotypic profiles of PHIV and PHEU markedly differed from those of geographically-matched contemporary HIV-unexposed infants. The frequency of regulatory T and B cells (Treg, Breg) of PHIV and PHEU displayed two patterns of associations: FOXP3+CD25+ Treg positively correlated with CD4+ T cell numbers; while TGF-b+ Treg and IL10+ Treg and Breg positively correlated with the frequencies of inflammatory and activated T cells. Moreover, the frequencies of activated and inflammatory T cells of PHIV and PHEU positively correlated with the frequency of immature B cells. Correlations were not affected by HIV status and persisted over time. PHIV and PHEU antibody responses to RV5 positively correlated with CD4+ T cell counts and negatively with the proportion of immature B cells, similarly to what has been previously described in chronic HIV infection. Unique to PHIV and PHEU, anti-RV5 antibodies positively correlated with CD4+/CD8+FOXP3+CD25+% and negatively with CD4+IL10+% Tregs. In conclusion, PHEU shared with PHIV abnormal B and T cell phenotypic profiles. PHIV and PHEU antibody responses to RV5 were modulated by typical HIV-associated immune response modifiers except for the association between CD4+/CD8+FOXP3+CD25+ Treg and increased antibody production.